Analysis of External Factors Affecting the Rumah Anggur Ardo Nursery Business Using PESTEL and Porter's Five Forces: External Factors Affecting the Rumah Anggur Ardo Nursery Business Using PESTEL and Porter's Five Forces - manalu, tresia; Nadya Stefania Hutauruk; Sri Rahayu Sinaga; Riza Indriani (Jurnal Ecoment Global, 2025)
Objectives: This study aims to analyze the external factors affecting the sustainability of the Rumah AnggurArdo nursery business in Medan, Indonesia, using the PESTEL framework and Porter's Five Forces. Thestudy highlights how political, economic, social, technological, environmental, and legal conditions, as wellas the competitive dynamics of the industry, shape opportunities and challenges for small agribusinessesbased on urban farming.Methods: The study used descriptive qualitative methods through in-depth interviews with businessowners and literature review. Data were collected using a structured questionnaire that identified politicalsupport, market behavior, technological adaptation, environmental risks, and legal status, along with anindustry competition analysis.Findings: Results show that Rumah Anggur Ardo operates in a relatively favorable competitiveenvironment with low rivalry and minimal threat of substitution. The main opportunity comes from thetrend of urban farming as a hobby, while the biggest challenges are high rainfall that damages seedlingsand the absence of material support from the government. Consumers prioritize seedling quality and post-sales consultation services over price, making service differentiation a key competitive advantage.Originality/Value: Unlike previous studies that emphasized profit-oriented agribusiness and internalfactors, this study presents a new perspective by analyzing hobby-based nursery businesses through anexternal environmental approach.Practical/Policy Implications: The research findings emphasize the importance of governmentfacilitation, development of local breeding farms, and investment in greenhouse facilities. For practitioners,strengthening community engagement and utilizing digital platforms are key strategies to maintaincompetitiveness.Keywords: External, PESTEL, Porter, Agribusiness